Mediator Judge In Court: Approach To Local Wisdom In Banyumas Community - Indriati Amarini; Marsitiningsih Marsitiningsih; Ratna Kartikawati (Program Studi Hukum Keluarga Islam, 2023)
Court mediation is regulated in the Civil Procedure Code under the term peacemaking. Court mediation is a concept developed by the Dutch which is still used in the settlement of civil disputes in Indonesian courts. However, the implementation of mediation in court is not optimal. This research aims to analyze the causes of the unsuccessful implementation of mediation in court. The research method used is doctrinal research sourced from legislation, literature and scientific journals. The results showed that the success of mediation in court in resolving civil disputes lies in the role of judges as mediators. Judges serving in Banyumas must have sufficient knowledge about the philosophy of dispute resolution in Banyumas society. There are four types of Banyumas local wisdom that become the internal capital of dispute resolution to keep it running lightly, honestly, and firmly, egalitarian, traditional, deliberation and these five principles become the basis for Banyumas people to live in harmony and horizontal harmony, so as to create a safe and peaceful life.Mediasi pengadilan diatur dalam KUHAP dengan istilah perdamaian. Mediasi pengadilan merupakan konsep yang dikembangkan oleh Belanda yang masih digunakan dalam penyelesaian sengketa perdata di pengadilan Indonesia. Namun pelaksanaan mediasi di pengadilan belum optimal. Penelitian ini bertujuan untuk menganalisis penyebab tidak berhasilnya pelaksanaan mediasi di pengadilan. Metode penelitian yang digunakan adalah penelitian doktrinal yang bersumber dari peraturan perundang-undangan, literatur dan jurnal ilmiah. Hasil penelitian menunjukkan bahwa keberhasilan mediasi di pengadilan dalam penyelesaian sengketa perdata terletak pada peran hakim sebagai mediator. Hakim yang bertugas di Banyumas harus memiliki pengetahuan yang cukup tentang filosofi penyelesaian sengketa dalam masyarakat Banyumas. Ada empat jenis kearifan lokal Banyumas yang menjadi modal internal penyelesaian sengketa agar tetap berjalan ringan, jujur, dan tegas, egaliter, tradisional, musyawarah dan kelima prinsip tersebut menjadi landasan bagi masyarakat Banyumas untuk hidup rukun dan harmonis secara horizontal, sehingga tercipta kehidupan yang aman dan damai.